The effect of personal protective equipment on emergency airway management by emergency physicians: a mannequin study. (April 2016) - Wang, Chung-Cheng; Chaou, Chung-Hsien; Tseng, Chiung-Yao; Lin, Chih-Chuan
Abstract : Objective: Emergency medical personnel are at risk of secondary contamination when treating victims of chemical–biological–radiological–nuclear incidents. Hence, it is crucial to train them on the appropriate management of patients involved in chemical–biological–radiological–nuclear incidents. Personal protective equipment (PPE) plays an important role in treating patients suffering from various types of poisoning. However, very few studies have examined whether the use of PPE impedes airway management in an emergency department setting. The present study evaluated the effect of PPE on physicians' performance of emergency airway management using mannequins. Methods: Forty emergency physicians with 1–4 years of experience participated, and were divided by years of experience (1–2 vs. 3–4 years). Each participant both intubated a tracheal tube and inserted a laryngeal mask airway into a mannequin, with and without wearing protection using preassembled intubation aids. The intubation time for both methods was assessed along with participants' preferences and experiences in airway management. Results: The mean (SD) times to successful tracheal tube/mask placement with and without protection were similar [tracheal tube: 17.86 s (6.38) vs. 17.83 s (11.13), P =0.99; laryngeal mask: 10.51 s (4.39) vs. 9.65 s (3.29), P =0.32]. Conclusion: Protective equipment had no effect on physicians' emergency airway placement time. The effect of wearing PPE is limited if postintubation care is excluded from the evaluation. Furthermore, intubation experience influenced participants' preferred approach for airway management. Abstract : Supplemental Digital Content is available in the text.